2019
DOI: 10.1097/mpa.0000000000001353
|View full text |Cite
|
Sign up to set email alerts
|

Induction Therapy in Localized Pancreatic Cancer

Abstract: Objectives Pancreatic cancer (PDAC) with localized stage includes resectable (RPC), borderline resectable (BRPC), or locally advanced unresectable (LAPC). Standard of care for RPC is adjuvant chemotherapy. There are no prospective randomized trials for best treatment of BRPC and LAPC. We evaluate the impact of induction chemotherapy on localized PDAC. Methods Charts of PDAC patients treated at Emory University between 2009 and 2016 were reviewed. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…These studies suggest the efficacy of neoadjuvant treatment, which is indicated for resectable, borderline resectable, and locally advanced PDAC. Shaib et al also reported that borderline resectable PDAC that received NAC even demonstrated more favorable prognosis than resectable PDAC that underwent upfront surgery [20]. In the present study, pT1 (primary tumor size of ≤ 2.0 cm) was marginally more frequent, degree of nodal metastasis was significantly lower, and rate of distant metastasis was significantly lower at laparotomy in the NAC group.…”
Section: Discussionsupporting
confidence: 54%
“…These studies suggest the efficacy of neoadjuvant treatment, which is indicated for resectable, borderline resectable, and locally advanced PDAC. Shaib et al also reported that borderline resectable PDAC that received NAC even demonstrated more favorable prognosis than resectable PDAC that underwent upfront surgery [20]. In the present study, pT1 (primary tumor size of ≤ 2.0 cm) was marginally more frequent, degree of nodal metastasis was significantly lower, and rate of distant metastasis was significantly lower at laparotomy in the NAC group.…”
Section: Discussionsupporting
confidence: 54%
“…161 In a multicenter retrospective analysis in Japan, it was reported that the MST prolongation effect of NAT surpassed upfront sur- In addition, many single-center retrospective analyses have reported the prolongation effect of MST on NAT. 29,[164][165][166][167][168][169] Two RCTs have recently been reported, which compared the efficacies of NAT and upfront surgery for BR-PDAC. Jang et al conducted an RCT for BR-PDAC, which compared a NAT group that underwent surgery after GEM-based CRT where the surgery group underwent postoperative CRT.…”
Section: Borderline Resectable Pdacmentioning
confidence: 99%
“…In addition, many single‐center retrospective analyses have reported the prolongation effect of MST on NAT 29,164‐169 . Two RCTs have recently been reported, which compared the efficacies of NAT and upfront surgery for BR‐PDAC.…”
Section: Multidisciplinary Treatmentmentioning
confidence: 99%
“…Besides, induction therapy helps prolong the survival of patients. A study analyzed the OS of 409 patients with localized PDAC treated with different therapies, and the result revealed that patients who underwent resection after induction therapy had a significantly longer survival time than those who had surgery directly ( 37 ).…”
Section: Discussionmentioning
confidence: 99%